Inhibiting effects of 5-substituted isatin-based Mannich bases on the corrosion of mild steel in hydrochloric acid solution - Singh A.K.; Quraishi M.A. (My University, 2025)
The inhibition effect of all the three Mannich bases against the corrosion of mild steel in 1 M HCl solution was studied by weight loss, electrochemical impedance spectroscopy (EIS), potentiodynamic polarization, and atomic force microscopy techniques. Data obtained from EIS studies were analyzed to model the corrosion inhibition process through appropriate equivalent circuit models. The adsorption of Mannich bases obeyed Langmuir adsorption isotherm. Both thermodynamic and activation parameters were calculated and discussed. Polarization curves indicate that they are mixed type of inhibitors. All the Mannich bases were adsorbed physically at lower concentration, whereas chemisorption was favored at higher concentration. The results obtained from weight loss, EIS, and Potentiodynamic polarization are in good agreement. © Springer Science+Business Media B.V. 2010.